A Labuta do coordenador de curso: Investigação a partir do Instituto de Ciências da Sociedade, na Universidade Federal do Oeste do Pará. - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
This work aims to understand the role of the undergraduate course coordinator at the Federal University of Western Pará (UFOPA), in light of Henry Mintzberg's "facts and folklore" theory. To achieve this, a contextualized analysis of the advancement of higher education in Brazil was conducted, along with an investigation into the challenges faced by coordinators at the Institute of Social Sciences (ICS), which offers five undergraduate programs. The research employed a qualitative methodological approach, involving documentary and bibliographic research as well as a case study. Data collection was carried out through structured interviews with 10 faculty members, including former and current coordinators and vice-coordinators of ICS courses, representing 50% of the management universe. The data obtained were analyzed using visual tools such as a "Word Cloud," created with Canva software, to identify the frequency and relevance of terms used by participants. The results indicated a widespread perception of inadequate technical preparation among coordinators for their roles. Additionally, difficulties in financial management, personnel management, and task organization were highlighted, often resulting from workload overload and unclear institutional responsibilities. It is concluded that there is a need to strengthen institutional support through training, clear role definitions, and improved management processes so that they can promote more effective academic management, benefiting faculty and the institution as a whole.
Keywords: Coordenador de Curso; Fatos e Folclore; Gestão Pública; Instituto de Ciências da Sociedade; CNPQ:: CIÊNCIAS HUMANAS